2012
DOI: 10.1007/s00262-012-1257-x
|View full text |Cite
|
Sign up to set email alerts
|

Combined immunotherapy with Listeria monocytogenes-based PSA vaccine and radiation therapy leads to a therapeutic response in a murine model of prostate cancer

Abstract: Radiation therapy (RT) is an integral part of prostate cancer treatment across all stages and risk groups. Immunotherapy using a live, attenuated, Listeria monocytogenes-based vaccines have been shown previously to be highly efficient in stimulating anti-tumor responses to impact on the growth of established tumors in different tumor models. Here, we evaluated the combination of RT and immunotherapy using Listeria monocytogenes-based vaccine (ADXS31-142) in a mouse model of prostate cancer. Mice bearing PSA-ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 33 publications
(21 citation statements)
references
References 64 publications
1
20
0
Order By: Relevance
“…To our knowledge, our report is only the second preclinical study investigating the therapeutic potential of combining RT and a Lm -based vaccine 39 . By focusing on evaluating the local tumor microenvironment, our data extend the earlier finding by Hannan et al that a similar combinatorial strategy results in additive effects on systemic immune responses 39 …”
Section: Discussionsupporting
confidence: 78%
“…To our knowledge, our report is only the second preclinical study investigating the therapeutic potential of combining RT and a Lm -based vaccine 39 . By focusing on evaluating the local tumor microenvironment, our data extend the earlier finding by Hannan et al that a similar combinatorial strategy results in additive effects on systemic immune responses 39 …”
Section: Discussionsupporting
confidence: 78%
“…Although many studies have shown that RT induces tumorspecific immune responses (26)(27)(28)(29)46), our study demonstrates that the generation of tumor-specific CTLs (CD8 + OVA-tetramer + cells) is increased by the combination of RT and G-CSF. In addition, we demonstrated that ROS produced by G-CSF-stimulated RT-Ns are involved in the amplification of tumor-specific CTLs.…”
Section: Discussionmentioning
confidence: 77%
“…17 In preclinical studies using a murine prostate tumor model, it has furthermore been shown that the combination of Lm-based PSA (prostate specific antigen) immunotherapy and radiation therapy was more effective for the treatment of established tumors than either of the 2 treatment modalities used alone, with the combinatorial treatment demonstrating a multifold increase in PSA-specific cytotoxic T lymphocytes (CTLs) as well as a significant increase in CTL infiltration of tumor tissues. 18 The immunotherapeutic efficacy of Lm-based vectors has been further improved when combined with anti-PD-1 antibodies. 19 In a metastatic model of hepatic colorectal cancer, an AH1 peptide-expressing Lm strain elicited potent cytotoxic tumorspecific CD8 + T cell responses that could cure mice of hepatic metastasis and subsequently protect from tumor re-challenge.…”
Section: Anti-tumor Lm-based Immunotherapymentioning
confidence: 99%